Karakteristik Struktur Kristal In2Se3 Hasil Preparasi Dengan Metode Bridgman - Ulikaryani, Ulikaryani; Sodikin, Jenal; Akhlis Sarihidaya Laksana, Nur; Satria Jati, Unggul; Kristiningsih, Ari (P3M Politeknik Negeri Cilacap, 2023)
Apart from using silicon material, thin-layer solar cells can be made from various types of semiconductor materials, such as a combination of groups III and VI. In solar cell applications, these materials are usually used as n-type coatings. This study not only aimed to determine the crystal structure and the effect of annealing temperature on the crystal lattice parameters but also to determine the chemical composition and surface morphological structure of the crystals formed from the preparation. The crystal growth process was carried out using the Bridgman method with different heating patterns. The temperature in both annealing temperatures is 200oC and 250oC. The physical properties of the prepared In2Se3 crystals were characterized using XRD, SEM, and EDAX. XRD Characterization was used to determine the crystal structure, while SEM and EDAX characterization was used to determine the surface morphology and chemical composition of the crystals. The result of the XRD characterization showed that the formed In2Se3 crystals were polycrystals with a hexagonal structure. Based on the diffractogram obtained, the In2Se3 crystalline heating 1 has better quality. EDAX analysis showed that the In2Se3 crystals were composed of elements of In and Se with a mole ratio of 2:9, while the SEM characterization showed that the color of the surface morphology of the In2Se3 crystals was not homogeneous.